Studies in macroeconomic theory : employment and inflation - Phelps, Edmund S. (New York : Academic Press, 1979)
This volume reprints 17 papers by Phelps that were originally published between 1965 and 1978, together with one previously unpublished paper from 1959 and some newly written material in the form of seven brief commentaries on the origins and aims of the papers and a synthetic introductory essay laying out a theory of price, wage, and employment fluctuations. Phelps's work is deep, insightful, and technically challenging. Many of the reprinted papers are well known and have been influential in the rapid development of macroeconomic analysis in recent years.
Volume 1.
Includes bibliographical references.
rpm 03/04/2018
Loans
Keywords: Macroeconomics